PENGARUH PERENDAMAN DALAM AIR HANGAT TERHADAP KANDUNGAN FORMALIN PADA MIE BASAH DARI TIGA PRODUSEN YANG DIJUAL DI PASAR JOHAR SEMARANG - aqnes budiarti; supriyanti supriyanti; siti musinah (Universitas Wahid Hasyim Semarang, 2009)
ABSTRACTIt is assumed that the use of formalin in fresh noddles is still relatively high since its use not only prolongs the market life of the noddles but also make them tougher, brighter and non-adhesive. This research was intended to (1) analyze the presence of formalin in fresh noddles, (2) find out the levels of formalin contained in fresh noddles produced by three producers and sold in Johar Market, Semarang City and (3) find out the effects of bathing the noddles in warm water on the formalin contents.This was an experimental research with descriptive analyses. Employing a convenient sampling technique, the samples for this research were taken from the noddles produced by three producers and sold at Johar Market, Semarang City. To test the presence of formalin in the noddles, a chromatropatory-acid method was used. The samples containing formalin were analyzed using a spectrophotometer at an A of 569 nm. The samples were bathed for 15 minutes at temperatures of 40° C and 50° C. The effects of the bathing were analyzed by comparing the formalin contents before and after the bathingThe analyses showed that the fresh noddles produced by Kaligawe, Boja and Lamper producers contained 230,749 ± 18,092 mg/kg, 271,749 ± 18,088 mg/kg and 250,999 ± 18,090 mg/kg respectively. The comparison of the formalin contents before and after the bathing at 40° C showed significant differences. The comparison of the formalin contents before and after the bathing at 50° C also showed significant differences. The comparison of the formalin contents after the bathing at 40° C and 40° C also showed significant differences; the 40° C bathing reduced 39.77% of the formalin content, while the 50° C bathing reduced 65.42%.Keywords: Formalin, Fresh Noddles, Bathing and Warm Water